2015
DOI: 10.1021/acs.jmedchem.5b00659
|View full text |Cite
|
Sign up to set email alerts
|

N-Sulfonyl-aminobiaryls as Antitubulin Agents and Inhibitors of Signal Transducers and Activators of Transcription 3 (STAT3) Signaling

Abstract: A series of N-sulfonyl-aminobiaryl derivatives have been examined as novel antitubulin agents. Compound 21 [N-(4'-cyano-3'-fluoro-biphenyl-2-yl)-4-methoxy-benzenesulfonamide] exhibits remarkable antiproliferative activity against four cancer cell lines (pancreatic AsPC-1, lung A549, liver Hep3B, and prostate PC-3) with a mean GI50 value of 57.5 nM. Additional assays reveal that 21 inhibits not only tubulin polymerization but also the phosphorylation of STAT3 inhibition with an IC50 value of 0.2 μM. Four additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 23 publications
(65 reference statements)
0
17
1
Order By: Relevance
“…1B ). Compared with our previous finding, MPT0G066 exert its antiproliferative effect most efficaciously in ovarian cancer cells 11 . Further, MTT assay showed that MPT0G066 repressed SKOV3 and A2780 cell viability with an IC 50 value of 0.44 μM and 0.45 μM respectively ( Fig.…”
Section: Resultscontrasting
confidence: 82%
“…1B ). Compared with our previous finding, MPT0G066 exert its antiproliferative effect most efficaciously in ovarian cancer cells 11 . Further, MTT assay showed that MPT0G066 repressed SKOV3 and A2780 cell viability with an IC 50 value of 0.44 μM and 0.45 μM respectively ( Fig.…”
Section: Resultscontrasting
confidence: 82%
“…Previously, we have screened growth inhibition activities of arylsulfonamide compounds designed as Stat3 inhibitors against pancreatic cancer cell lines 12 , as Stat3 activation is important for cancer progression 3 . According to the results of cell growth inhibition activities by using the SRB assay, LTP-1 showed most effective growth inhibition activity with GI 50 values of 0.23 ± 0.01 and 0.42 ± 0.16 μM in AsPC-1 and PANC-1 cells, respectively ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2A using a cell-free tubulin polymerization assay. Since Stat3 and tubulin have been reported that physically associate with each other 18 19 , LTP-1, which was previously designed as a Stat3 inhibitor 12 , may cause tubulin depolymerization partly due to Stat3 inhibition effect in cell level and lead to potentiate the LTP-1-induced mitotic arrest to reach plateau phase that no dose-dependent effect could be seen under LTP-1 treatment ( Fig. 3C ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations